Soil Sterilization Eliminates Beneficial Microbes That Provide Natural Pest Suppression Ecosystem Services Against Radopholus similis and Fusarium Oxysporum V5w2 in the Endosphere and Rhizosphere of Tissue Culture Banana Plants - Ochieno, Dennis M. W. (Frontiers in Sustainable Food Systems, 2022)
Endosphere and rhizosphere microbes offer plant growth promotion and pest suppression ecosystem services in banana-based agroecosystems. Interest has been growing towards the use of such beneficial microbes in protecting vulnerable tissue culture banana plants against Radopholus similis and Fusarium oxysporum. A screenhouse experiment with potted tissue culture banana plants was conducted using sterile and non-sterile soil to investigate the effect of soil biota on R. similis and F. oxysporum. R. similis-inoculated plants in sterile soil were smaller, had more dead roots, higher nematode density, and produced fewer and smaller leaves, than those from non-sterile soil. Rhizosphere density of R. similis was lower in non-sterile than in sterile soil. For all plant growth-related parameters, no differences were recorded between those inoculated with R. similis only, and those co-inoculated with the nematode and F. oxysporum. Banana roots inoculated with F. oxysporum were lighter in colour than those without the fungus. Independent or combined inoculation of banana plants with F. oxysporum and R. similis resulted in lower optical density of root extracts. In vitro assays indicated the presence of Fusarium spp. and other root endophytic microbes that interacted antagonistically with the inoculated strain of F. oxysporum. It is concluded that, soil sterilization eliminates beneficial microbes that provide natural pest suppression ecosystem services against R. similis and F. oxysporum in the endosphere and rhizosphere of tissue culture banana plants.